Archaea and Bacteria Acclimate to High Total Ammonia in a Methanogenic Reactor Treating Swine Waste - Esquivel-Elizondo, S.; Parameswaran, P.; Delgado, A. G.; Maldonado, J.; Rittmann, B. E.; Krajmalnik-Brown, R. (My University, 2016)
Inhibition by ammonium at concentrations above 1000mgN/L is known to harm the methanogenesis phase of anaerobic digestion. We anaerobically digested swine waste and achieved steady state COD-removal efficiency of around 52% with no fatty-acid or H-2 accumulation. As the anaerobic microbial community adapted to the gradual increase of total ammonia-N (NH3 -N) from 890 +/- 295 to 2040 +/- 30 mg/L, the Bacterial and Archaeal communities became less diverse. Phylotypes most closely related to hydrogenotrophic Methanoculleus (36.4%) and Methanobrevibacter (11.6%), along with acetoclastic Methanosaeta (29.3%), became the most abundant Archaeal sequences during acclimation. This was accompanied by a sharp increase in the relative abundances of phylotypes most closely related to acetogens and fatty-acid producers (Clostridium, Coprococcus, and Sphaerochaeta) and syntrophic fatty-acid Bacteria (Syntrophomonas, Clostridium, Clostridiaceae species, and Cloacamonaceae species) that have metabolic capabilities for butyrate and propionate fermentation, as well as for reverse acetogenesis. Our results provide evidence countering a prevailing theory that acetoclastic methanogens are selectively inhibited when the total ammonia-N concentration is greater than similar to 1000 mgN/L. Instead, acetoclastic and hydrogenotrophic methanogens coexisted in the presence of total ammonia-N of similar to 2000 mgN/L by establishing syntrophic relationships with fatty-acid fermenters, as well as homoacetogens able to carry out forward and reverse acetogenesis.
Citation: Esquivel-Elizondo, S., Parameswaran, P., Delgado, A. G., Maldonado, J., Rittmann, B. E., & Krajmalnik-Brown, R. (2016). Archaea and Bacteria Acclimate to High Total Ammonia in a Methanogenic Reactor Treating Swine Waste. Archaea-an International Microbiological Journal, 10. doi:10.1155/2016/4089684
Keywords: Complete Genome Sequence; 16S Ribosomal-Rna; Microbial Communities; Acetate Oxidation; Propionate Oxidation; Oxidizing Bacterium